Sosialisasi dan Implementasi Pendekatan Kecerdasan Majemuk dalam Pembelajaran di Sekolah Dasar Mitra Kota Mataram - Darmiany Darmiany; Nurkhaerat Alimuddin; Ni Made Yeni Suranti; Mega Puspita Sari; Nurwahidah Nurwahidah (Indonesian Journal of Education and Community Services, 2025)
This community service activity aims to improve the understanding of Mitra Elementary School teachers in Mataram City regarding the concept and application of the Multiple Intelligences approach in the learning process. Multiple intelligences developed by Howard Gardner emphasizes that each individual has various types of unique intelligences and can be optimally developed through appropriate learning strategies. However, the use of this approach is still limited in elementary school environments, especially in the planning and implementation of learning that is centered on student potential. Through this socialization activity, teachers are given an understanding of the eight types of multiple intelligences, their characteristics, and learning strategies that are appropriate for each intelligence. The method of implementing the activity is in the form of lectures, interactive discussions, and simple case studies. The evaluation results show that this activity has succeeded in increasing participants' insight into the diversity of student potential and the importance of differentiation of learning strategies. It is hoped that this activity will be the first step for teachers to be more adaptive and innovative in developing inclusive learning that is oriented towards the uniqueness of each student.